Overweight, Obesity and girth of Australian preSchoolers: Prevalence and socioeconomic correlates - Carlin, J; Sawyer, M; Hardy, P; Canterford, L; Wake, M (My University, 2007)
Drawing on data from Wave 1 of the Longitudinal Study of Australian Children, this study examined the prevalence of overweight and obesity in Australian four to five year old children, and investigated associations between socio-economic characteristics and overweight/obesity, and socio-economic characteristics and waist circumference. The findings confirm a high prevalence of overweight and obesity in Australian preschoolers, and suggest that the clearest indicators of a high body mass index status in these children are: speaking a language other than English, particularly for boys; Indigenous status; and being the lower social disadvantage quintile. Waist circumference was not related to any socio-economic variable.
International Journal of Obesity
Keywords: Health; Child Development -- Sleep; Health -- Obesity; Child Development; Childhood and child development; Health and wellbeing; Health; Child Development; Obesity; Sleep; Childhood and child development; Health and wellbeing